2018
DOI: 10.1186/s13062-018-0207-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics integration for neuroblastoma clinical endpoint prediction

Abstract: BackgroundHigh-throughput methodologies such as microarrays and next-generation sequencing are routinely used in cancer research, generating complex data at different omics layers. The effective integration of omics data could provide a broader insight into the mechanisms of cancer biology, helping researchers and clinicians to develop personalized therapies.ResultsIn the context of CAMDA 2017 Neuroblastoma Data Integration challenge, we explore the use of Integrative Network Fusion (INF), a bioinformatics fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Regarding the network architecture, models relying on four layer networks perform the best for both clinical outcomes (Table 3). This is in agreement with previous studies that have reported that such relatively small networks (i.e., with three or four layers) can efficiently predict clinical outcomes of kidney cancer patients [17] or can capture relevant features for survival analyses of a neuroblastoma cohort [12].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the network architecture, models relying on four layer networks perform the best for both clinical outcomes (Table 3). This is in agreement with previous studies that have reported that such relatively small networks (i.e., with three or four layers) can efficiently predict clinical outcomes of kidney cancer patients [17] or can capture relevant features for survival analyses of a neuroblastoma cohort [12].…”
Section: Discussionsupporting
confidence: 92%
“…All shallow and DL models (including class balancing experiments) were trained within the DAP previously developed by FBK within the MAQC-II and SEQC challenges [31,32], the U.S. FDA initiatives for reproducibility of biomarkers. Briefly, our DAP uses a 10 × 5−fold stratified CV on TR to get a ranked feature list and a set of classification metrics [33], including the MCC. Data were rescaled in the interval [ −1, 1] (for shallow learning) or centered and scaled to unit variance (for DL) before undergoing classification: rescaling parameters from TR were used for rescaling both TR and TS subsets, so to avoid information leakage.…”
Section: Predictive Modeling Strategymentioning
confidence: 99%
“…Obviously, a great debate about this procedure and all early and late risks linked to it arose: blow out of the blind end, reactivation of CD in the excluded segment with abdominal pain and infections, deprivation of a large portion of the colon for water absorption. Eventually, bypass procedure was abandoned due to findings of adenocarcinoma occurring in the excluded segment [ 19 , 38 40 ]. Surgical resection of the diseased bowel emerged as the procedure of choice for most patients with CD of the terminal ileum or with ileo-colitis, including complicated cases [ 41 ].…”
Section: Surgical Management and CD Recurrencementioning
confidence: 99%